Preparation and sintering process of black zirconia composite material
Color uniformity is solved by using zirconia recovery material, a mixture of zirconia and graphene in the sintering process of black zirconia ceramic materials, and ball milling and spray-drying treatment, combining temperature isostatic pressure and controlling the sintering temperature. and mechanical properties, efficient resource utilization and excellent material properties are achieved.
Patent Information
- Application Number
- CN202411687202.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-25
AI Technical Summary
It is difficult to ensure color uniformity in the existing black zirconia ceramic materials in the sintering process, especially when using zirconia recycling materials, the purity and activity are low, which affects the blackness and color consistency of the material.
The zirconia recovery material, a mixture of zirconia and graphene was used for ball milling, and the primary powder was made by spray drying technology, and mixed uniformly with black pigment, binder and dispersant. After temperature isostatic pressure treatment and glue discharge sintering , and finally control the sintering temperature and cooling rate to ensure excellent color uniformity and mechanical properties.
The utilization rate of zirconia recovery materials and the utilization rate of resources are improved, the color uniformity and mechanical properties of black zirconia composite materials are ensured, and the phenomenon of product cracking is avoided.
Smart Images

Figure CN119430920A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of ceramic product preparation technology, and in particular relates to a preparation and sintering process of a black zirconium oxide composite material. Background Art
[0002] In recent years, with the development of black zirconia ceramics, black zirconia ceramics have been increasingly used in the fields of electronic products, decoration, daily necessities, medicine, piezoelectric ceramics, sensor ceramics, etc., such as mobile phone cases, watch cases, knives and other products. There are two main process routes for the traditional preparation of black zirconia ceramics. One is the vacuum blackening method, which generally requires a blackening temperature of about 1500°C. The temperature is relatively high and the fired product is usually accompanied by different proportions of red and white phenomena, and the prepared zirconia has poor blackness; the other is to add black colorant to the zirconia matrix for preparation.
[0003] The existing Chinese patent with publication number CN108640678B discloses a black zirconia ceramic material and a preparation method and product of black zirconia ceramic. The black zirconia ceramic material includes the following components in weight percentage: 80% to 95% of zirconium oxide; 2.5% to 5% of yttrium oxide; and a balance of black pigment. The black pigment includes the following components in weight percentage: 0% to 40% of iron oxide, 0% to 30% of chromium oxide, 10% to 30% of cobalt oxide, 0% to 10% of manganese oxide, 0% to 10% of nickel oxide, 5% to 30% of aluminum oxide, 0% to 6% of zinc oxide, and 0% to 5% of silicon oxide. The weight percentage of iron oxide, chromium oxide, cobalt oxide, manganese oxide, nickel oxide, aluminum oxide, zinc oxide, and silicon oxide is a percentage of the total weight of the black pigment.
[0004] Although the above preparation method has pure color and high blackness after sintering, with the emphasis on ecological environment and the need for sustainable development, in the research on material preparation technology, in order to improve the recycling of zirconia, the use of added zirconia recycled materials to improve the utilization rate of raw materials has emerged. However, the purity and activity of zirconia recycled materials are low after sintering and grinding. Due to the limitations of the sintering process, it is difficult to ensure the color uniformity of the black zirconia composite material by adding different proportions of zirconia recycled materials. Summary of the invention
[0005] The purpose of this application is to provide a preparation and sintering process of a black zirconia composite material in order to address the above-mentioned technical problems, increase the utilization rate of recycled zirconia materials, improve resource utilization, and ensure the color uniformity of the black zirconia composite material.
[0006] The present application provides a preparation and sintering process of a black zirconium oxide composite material, the specific steps of which include:
[0007] S1, taking zirconium oxide recycled material, zirconium oxide, and graphene and mixing them, the weight percentage of which is recorded as: (15-20): (70-75): (5-10);
[0008] S2, putting the mixed zirconia recycled material, zirconia, and graphene mixture into a ball mill for uniform mixing, and the ball-milled mixture is made into primary powder by spray drying technology;
[0009] S3, uniformly mixing the primary powder, black pigment, binder and dispersant, pre-pressing with a mold and performing warm isostatic pressing to obtain a green body;
[0010] S4, debinding and sintering the green body after static pressing to obtain a black zirconia composite material;
[0011] S5, after sintering is completed, the temperature is lowered;
[0012] The sintering temperature in step S4 is controlled between 1350° C. and 1550° C., and the holding time is 2 to 6 hours.
[0013] Furthermore, in step S1, the zirconium oxide recovery material is fully washed with hydrochloric acid and then calcined at 700°C.
[0014] Furthermore, in step S2, the particle size of the primary powder is below 80 nm.
[0015] Furthermore, in step S3, the black colorant is iron oxide, chromium oxide, cobalt oxide, manganese oxide, nickel oxide, aluminum oxide, zinc oxide, and silicon oxide.
[0016] Furthermore, in step S3, the pressing parameters of warm isostatic pressing are: temperature 100°C-150°C, isostatic pressing pressure 200-300 MPa, and holding time 150-180 min.
[0017] Furthermore, in step S3, the dispersant is 3%-5% by weight of the primary powder, and the dispersant is one or more of polymethyl methacrylate, ammonium polyacrylate, sodium tripolyphosphate, polyethylene glycol and sodium hexametaphosphate.
[0018] Furthermore, in step S4, the temperature for debinding is 800°C-900°C, and the time for debinding is 40h-80h.
[0019] Furthermore, in step S4, the heating rate of the sintering temperature is first controlled to be 10-25°C / min, and the temperature is stopped for 10 minutes every time the temperature rises by 100°C.
[0020] Furthermore, in step S4, the cooling rate is first controlled to be 1-3°C / 5 minutes to cool down to 550°C, then the cooling rate is controlled to be 2-5°C / minute to cool down to 100°C, and finally the temperature is cooled to room temperature.
[0021] The beneficial effects of this application are:
[0022] 1. The zirconium oxide recycled material, zirconium oxide and graphene are sanded, mixed with black pigment, and then molded, debonded, sintered and cooled in sequence to obtain a black zirconium oxide composite material.
[0023] 2. The mixture of zirconia recycled material, zirconia and graphene is ground by a ball mill to improve the grinding efficiency. At the same time, the graphene is evenly mixed with the zirconia recycled material and zirconia to improve the activity of the zirconia recycled material during sintering and improve the color uniformity.
[0024] 3. By adding graphene, it can also prevent the product from cracking and improve the mechanical properties of the black zirconia composite material.
[0025] 4. By setting stable heating and cooling rates, the stable activation of the zirconia recycled material is ensured to prevent the product from cracking. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a process flow chart of the preparation and sintering process of the black zirconium oxide composite material of the present application; DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.
[0028] The terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.
[0029] The following provides a detailed description of the embodiments of the present application through specific embodiments and their application scenarios in conjunction with the accompanying drawings.
[0030] Embodiment 1:
[0031] A preparation and sintering process of a black zirconium oxide composite material is provided, and the specific steps include:
[0032] S1, taking zirconium oxide recycled material, zirconium oxide, and graphene and mixing them in a weight percentage of 15:70:5;
[0033] S2, putting the mixed zirconia recycled material, zirconia, and graphene mixture into a ball mill for uniform mixing, and the ball-milled mixture is made into primary powder by spray drying technology;
[0034] S3, uniformly mixing the primary powder, black pigment, binder and dispersant, pre-pressing with a mold and performing warm isostatic pressing to obtain a green body;
[0035] S4, debinding and sintering the green body after static pressing to obtain a black zirconia composite material;
[0036] S5, after sintering is completed, the temperature is lowered;
[0037] The sintering temperature in step S4 is controlled at 1400° C. and the holding time is 4 hours.
[0038] Furthermore, in step S1, the zirconium oxide recovery material is fully washed with hydrochloric acid and then calcined at 700°C.
[0039] Furthermore, in step S2, the particle size of the primary powder is below 80 nm.
[0040] Furthermore, in step S3, the black colorant is iron oxide, chromium oxide, cobalt oxide, manganese oxide, nickel oxide, aluminum oxide, zinc oxide, and silicon oxide.
[0041] Furthermore, in step S3, the pressing parameters of warm isostatic pressing are: temperature 100° C., isostatic pressing pressure 250 MPa, and holding time 160 min.
[0042] Furthermore, in step S3, the dispersant is 3% by weight of the primary powder, and the dispersant is one or more of polymethyl methacrylate, ammonium polyacrylate, sodium tripolyphosphate, polyethylene glycol and sodium hexametaphosphate.
[0043] Furthermore, in step S4, the temperature for debinding is 800° C., and the time for debinding is 40 hours.
[0044] Furthermore, in step S4, the heating rate of the sintering temperature is controlled to be 10° C. / min, and the temperature is stopped for 10 minutes every time the temperature rises by 100° C.
[0045] Furthermore, in step S4, the temperature is firstly cooled at a rate of 1°C / 5 minutes to 550°C, then at a rate of 2°C / minute to 100°C, and finally to room temperature.
[0046] Embodiment 2:
[0047] A preparation and sintering process of a black zirconium oxide composite material is provided, and the specific steps include:
[0048] S1, taking zirconium oxide recycled material, zirconium oxide, and graphene and mixing them in a weight percentage of 15:75:5;
[0049] S2, putting the mixed zirconia recycled material, zirconia, and graphene mixture into a ball mill for uniform mixing, and the ball-milled mixture is made into primary powder by spray drying technology;
[0050] S3, uniformly mixing the primary powder, black pigment, binder and dispersant, pre-pressing with a mold and performing warm isostatic pressing to obtain a green body;
[0051] S4, debinding and sintering the green body after static pressing to obtain a black zirconia composite material;
[0052] S5, after sintering is completed, the temperature is lowered;
[0053] The sintering temperature in step S4 is controlled at 1400° C. and the holding time is 4 hours.
[0054] Furthermore, in step S1, the zirconium oxide recovery material is fully washed with hydrochloric acid and then calcined at 700°C.
[0055] Furthermore, in step S2, the particle size of the primary powder is below 80 nm.
[0056] Furthermore, in step S3, the black colorant is iron oxide, chromium oxide, cobalt oxide, manganese oxide, nickel oxide, aluminum oxide, zinc oxide, and silicon oxide.
[0057] Furthermore, in step S3, the pressing parameters of warm isostatic pressing are: temperature 100° C., isostatic pressing pressure 250 MPa, and holding time 160 min.
[0058] Furthermore, in step S3, the dispersant is 3% by weight of the primary powder, and the dispersant is one or more of polymethyl methacrylate, ammonium polyacrylate, sodium tripolyphosphate, polyethylene glycol and sodium hexametaphosphate.
[0059] Furthermore, in step S4, the temperature for debinding is 800° C., and the time for debinding is 40 hours.
[0060] Furthermore, in step S4, the heating rate of the sintering temperature is controlled to be 10° C. / min, and the temperature is stopped for 10 minutes every time the temperature rises by 100° C.
[0061] Furthermore, in step S4, the temperature is first cooled at a rate of 2°C / 5 minutes to 550°C, then at a rate of 3°C / minute to 100°C, and finally to room temperature.
[0062] Embodiment 3:
[0063] A preparation and sintering process of a black zirconium oxide composite material is provided, and the specific steps include:
[0064] S1, taking zirconium oxide recycled material, zirconium oxide and graphene and mixing them, the weight percentage of which is 20:75:5;
[0065] S2, putting the mixed zirconia recycled material, zirconia, and graphene mixture into a ball mill for uniform mixing, and the ball-milled mixture is made into primary powder by spray drying technology;
[0066] S3, uniformly mixing the primary powder, black pigment, binder and dispersant, pre-pressing with a mold and performing warm isostatic pressing to obtain a green body;
[0067] S4, debinding and sintering the green body after static pressing to obtain a black zirconia composite material;
[0068] S5, after sintering is completed, the temperature is lowered;
[0069] The sintering temperature in step S4 is controlled at 1400° C. and the holding time is 4 hours.
[0070] Furthermore, in step S1, the zirconium oxide recovery material is fully washed with hydrochloric acid and then calcined at 700°C.
[0071] Furthermore, in step S2, the particle size of the primary powder is below 80 nm.
[0072] Furthermore, in step S3, the black colorant is iron oxide, chromium oxide, cobalt oxide, manganese oxide, nickel oxide, aluminum oxide, zinc oxide, and silicon oxide.
[0073] Furthermore, in step S3, the pressing parameters of warm isostatic pressing are: temperature 100° C., isostatic pressing pressure 250 MPa, and holding time 160 min.
[0074] Furthermore, in step S3, the dispersant is 3%-5% by weight of the primary powder, and the dispersant is one or more of polymethyl methacrylate, ammonium polyacrylate, sodium tripolyphosphate, polyethylene glycol and sodium hexametaphosphate.
[0075] Furthermore, in step S4, the temperature for debinding is 800° C., and the time for debinding is 40 hours.
[0076] Furthermore, in step S4, the heating rate of the sintering temperature is first controlled to be 15° C. / min, and the temperature is stopped for 10 minutes every time the temperature rises by 100° C.
[0077] Furthermore, in step S4, the temperature is first cooled at a rate of 2°C / 5 minutes to 550°C, then at a rate of 3°C / minute to 100°C, and finally to room temperature.
[0078] Embodiment 4:
[0079] A preparation and sintering process of a black zirconium oxide composite material is provided, and the specific steps include:
[0080] S1, taking zirconium oxide recycled material, zirconium oxide, and graphene and mixing them in a weight percentage of 20:70:10;
[0081] S2, putting the mixed zirconia recycled material, zirconia, and graphene mixture into a ball mill for uniform mixing, and the ball-milled mixture is made into primary powder by spray drying technology;
[0082] S3, uniformly mixing the primary powder, black pigment, binder and dispersant, pre-pressing with a mold and performing warm isostatic pressing to obtain a green body;
[0083] S4, debinding and sintering the green body after static pressing to obtain a black zirconia composite material;
[0084] S5, after sintering is completed, the temperature is lowered;
[0085] The sintering temperature in step S4 is controlled at 1500° C. and the holding time is 5 hours.
[0086] Furthermore, in step S1, the zirconium oxide recovery material is fully washed with hydrochloric acid and then calcined at 700°C.
[0087] Furthermore, in step S2, the particle size of the primary powder is below 80 nm.
[0088] Furthermore, in step S3, the black colorant is iron oxide, chromium oxide, cobalt oxide, manganese oxide, nickel oxide, aluminum oxide, zinc oxide, and silicon oxide.
[0089] Furthermore, in step S3, the pressing parameters of warm isostatic pressing are: temperature 140° C., isostatic pressing pressure 260 MPa, and holding time 160 min.
[0090] Furthermore, in step S3, the dispersant is 5% by weight of the primary powder, and the dispersant is one or more of polymethyl methacrylate, ammonium polyacrylate, sodium tripolyphosphate, polyethylene glycol and sodium hexametaphosphate.
[0091] Furthermore, in step S4, the temperature for debinding is 850° C., and the time for debinding is 70 h.
[0092] Furthermore, in step S4, the heating rate of the sintering temperature is controlled to be 20°C / min, and the temperature is stopped for 10 minutes every time the temperature rises by 100°C.
[0093] Furthermore, in step S4, the temperature is first cooled at a rate of 2°C / 5 minutes to 550°C, then at a rate of 3°C / minute to 100°C, and finally to room temperature.
[0094] Next, we conducted experiments to observe the appearance of the black zirconium oxide composite materials prepared in the above Examples 1-4. The product surfaces were smooth and complete without cracks, warping, etc., and density, bending strength, Vickers hardness and color uniformity tests were conducted. The test results are shown in Table 1.
[0095] Table 1 Performance test results of black zirconia composite materials
[0096] <![CDATA[Density (g / cm 3 )]]> Flexural strength(MPa) Vickers hardness (HV) Color uniformity (ΔE) Embodiment 1 6.03 1575 1201 1.2 Embodiment 2 6.04 1581 1210 1.3 Embodiment 3 6.04 1583 1214 0.7 Embodiment 4 6.05 1592 1013 0.8
[0097] It can be seen from Table 1 that the smaller the color uniformity ΔE value is, the higher the uniformity is. The black zirconia composite material prepared by the present invention has excellent mechanical properties. When using recycled zirconia material, adding an appropriate amount of graphene material can improve the color uniformity of the black zirconia composite material.
[0098] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0099] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.
Claims
1. A preparation and sintering process of a black zirconium oxide composite material, characterized in that: The specific steps include: S1, taking zirconium oxide recycled material, zirconium oxide, and graphene and mixing them, the weight percentage of which is recorded as: (15-20): (70-75): (5-10); S2, putting the mixed zirconia recycled material, zirconia, and graphene mixture into a ball mill for uniform mixing, and the ball-milled mixture is made into primary powder by spray drying technology; S3, uniformly mixing the primary powder, black pigment, binder and dispersant, pre-pressing with a mold and performing warm isostatic pressing to obtain a green body; S4, debinding and sintering the green body after static pressing; S5, after sintering is completed, the temperature is lowered to obtain a black zirconium oxide composite material; The sintering temperature in step S4 is controlled between 1350° C. and 1550° C., and the holding time is 2 to 6 hours.
2. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S1, the zirconium oxide recovery material is fully washed with hydrochloric acid and then calcined at 700°C.
3. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S2, the primary powder particle size is below 80 nm.
4. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S3, the black colorant is iron oxide, chromium oxide, cobalt oxide, manganese oxide, nickel oxide, aluminum oxide, zinc oxide, and silicon oxide.
5. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S3, the pressing parameters of warm isostatic pressing are: temperature 100°C-150°C, isostatic pressing pressure 200-300 MPa, and holding time 150-180 min.
6. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S3, the dispersant accounts for 3% to 5% of the weight of the primary powder, and the dispersant is one or more of polymethyl methacrylate, ammonium polyacrylate, sodium tripolyphosphate, polyethylene glycol and sodium hexametaphosphate.
7. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S4, the temperature for debinding is 800° C.-900° C., and the time for debinding is 40 h-80 h.
8. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S4, the heating rate of the sintering temperature is first controlled to be 10-25°C / min, and the temperature is stopped for 10 minutes every time the temperature rises by 100°C.
9. The preparation and sintering process of the black zirconium oxide composite material according to claim 1, characterized in that: In step S4, the temperature is first cooled at a rate of 1-3°C / 5 minutes to 550°C, then cooled at a rate of 2-5°C / minute to 100°C, and finally cooled to room temperature.
Citation Information
Patent Citations
Black zirconia ceramic materials, preparation methods and products of black zirconia ceramics
CN108640678B
Graphite-based carbon material useful as graphene precursor, as well as method of producing the same
CA2894774A1
Method for reinforcing magnesium base composite material by zirconium oxide modified graphene
CN106893881A
Black zirconia ceramic and preparation method thereof
CN107043254A
Black zirconia ceramic and preparation method thereof
CN107555989A